Investigation of the Carbon Dioxide Centrifugal Compressor Working Process using Computational Fluid Dynamics Methods - Fateeva E.S.; Danilishin A.M.; Kozhukhov Y.V.; Kazantsev R.A. (Problems of the Regional Energetics)
The article investigates the carbon dioxide (CO₂) centrifugal compressor using computational fluid dynamics (CFD). CO₂ centrifugal compressors are used in refrigeration and cryogenic systems, power plants with subcritical and transcritical cycles, including Brayton cycle. This work is a part of a re-search effort aimed at developing a methodology for calculating the gas-dynamic characteristics of centrifugal compressor stages in refrigeration systems. The main objectives of the research are to investigate the three-dimensional viscous flow parameters of carbon dioxide in the centrifugal compressor flow path using CFD and to compare two approaches of taking into account the reality of gas during modeling comparison. Key tasks included: centrifugal compressor CFD model replicating an experimentally tested compressor geometry and operation, comparing simulated outputs against ex-perimental data, total-to-total isentropic efficiency calculation.Two real-gas modeling approaches were evaluated: Ansys CFX’s built-in real gas models and external tables of CO₂ properties. The most significant results are the describing the features of the carbon dioxide centrifugal compressor working process using both the built-in real gas models in Ansys CFX and imported tables of real gas properties and the demonstration of satisfactory agreement between simulation and experiment. The significance of the obtained results lies in increasing the efficiency of carbon dioxide centrifugal compressors in process units of refrigerating, cryogenic and power systems. Compressors efficiency improvement is provided by developed recommendations application for performance of working process CFD-modeling considering peculiarities of carbon dioxide in subcritical state in design calculations.